Impact of exogenous arginine, cysteine and methionine on the postharvest senescence of six green leafy vegetables - Muhammad Sohail (University of Birjand, 2021)
Purpose: This study examined the efficacy of aqueous dips containing the amino acids, L-arginine, L-cysteine and L-methionine, to inhibit the senescence of six leafy green vegetables pak choy, coriander, choy sum, spinach, parsley and rocket. Research method: Pak choy was dipped in amino acid solutions from 2-100 mM to determine the optimum concentration that inhibited senescence. The other vegetables were dipped in solutions with the optimal concentration. Senescence of the vegetables was assessed during storage at 10 °C in air containing 0.1 µL L1 ethylene by determining loss of green colour (designated as green life), ethylene production and respiration rates. Findings: For each amino acid, a dipping concentration of 5 mM was found optimal to inhibit senescence as shown by an extended green life and reduced ethylene production and respiration rates of all vegetables to a similar extent, except methionine which did not show a significant effect with rocket, and for spinach only reduced ethylene production. Limitations: No limitations were encountered. Originality/Value: Arginine and cysteine showed considerable potential for commercial use to extend the market life of many green vegetables and with their Generally Recognized As Safe (GRAS) status the amino acids should be a safe, consumer-acceptable treatment.